The regional dynamics of innovation: a comparative study of oil and gas industry development in Stavanger and Aberdeen. Issue 3 (6th June 2011) - Hatakenaka, Sachi; Westnes, Petter; Gjelsvik, Martin; Lester, Richard
This paper reports on a comparative case study of the development of local innovation systems in two key gateways to the North Sea oil and gas province: the Stavanger region on the southwest coast of Norway and the Aberdeen region in northeast Scotland. These two regions provide an ideal setting for a matched pair comparison, since the global market conditions and local geotechnical environment within which they developed into 'oil capitals' are strikingly similar. Despite these similarities, the development of local technological and industrial capabilities followed different paths in the two locations. Yet these differences do not appear to have led to significant differences in industrial competitiveness. Although Stavanger and Aberdeen are characterised by very different local innovation systems, the available evidence suggests that outcomes have been similar along significant dimensions of industry performance.